2022
DOI: 10.1093/gbe/evac036
|View full text |Cite|
|
Sign up to set email alerts
|

Strong Parallel Differential Gene Expression Induced by Hatchery Rearing Weakly Associated with Methylation Signals in Adult Coho Salmon (O. kisutch)

Abstract: Human activities and resource exploitation led to a massive decline of wild salmonid populations, consequently numerous conservation programs have been developed to supplement wild populations. However, many studies documented reduced fitness of hatchery-born relative to wild fish. Here, by using both RNA sequencing and Whole Genome Bisulfite Sequencing (WGBS), we show that of hatchery and wild born adult Coho Salmon (Oncorhynchus kisutch) originating from two previously studied river systems, early-life hatch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 71 publications
2
3
0
Order By: Relevance
“…Christie et al (2016) found a single generation in a hatchery environment altered the expression of over 700 genes in steelhead. Other research has found similar results (Leitwein et al, 2022), even in the absence of genetic differentiation between wild and hatchery populations (Le Luyer et al, 2017), and the potential for the epigenetic changes to be passed along to offspring (Leitwein et al, 2021; Venney et al, 2023). Though the duration of impacts remains unclear it is hypothesized that heritable epigenetic effects may alter the evolutionary trajectory of wild populations, which is a critical issue to evaluate where hatchery salmonids are allowed to or are able to breed with wild salmonids (Skinner & Nilsson, 2021).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Christie et al (2016) found a single generation in a hatchery environment altered the expression of over 700 genes in steelhead. Other research has found similar results (Leitwein et al, 2022), even in the absence of genetic differentiation between wild and hatchery populations (Le Luyer et al, 2017), and the potential for the epigenetic changes to be passed along to offspring (Leitwein et al, 2021; Venney et al, 2023). Though the duration of impacts remains unclear it is hypothesized that heritable epigenetic effects may alter the evolutionary trajectory of wild populations, which is a critical issue to evaluate where hatchery salmonids are allowed to or are able to breed with wild salmonids (Skinner & Nilsson, 2021).…”
Section: Discussionsupporting
confidence: 53%
“…Christie et al (2016) found a single generation in a hatchery environment altered the expression of over 700 genes in steelhead. Other research has found similar results (Leitwein et al, 2022), even in the absence of genetic differentiation between wild and hatchery populations (Le Luyer et al, 2017), and the potential for the epigenetic changes to be passed along to offspring (Leitwein et al, 2021;Venney et al, 2023).…”
Section: Hatchery Type Adversesupporting
confidence: 63%
“…While the epigenetic effects of hatchery rearing in salmonids are well-documented (Gavery et al, 2019, 2018; Koch et al, 2022; Le Luyer et al, 2017; Leitwein et al, 2021, 2022; Rodriguez Barreto et al, 2019; Venney et al, 2021; Wellband et al, 2021), the long-term stability of these changes after release into natural systems has not been extensively studied, nor has the sex-specificity of the effects of hatchery rearing on the methylome. Here we showed that hatchery rearing led to general and sex-specific changes in Atlantic salmon fin DNA methylation that persisted until the salmon returned to spawn, consistent with similar results in Coho salmon returning to freshwater after eighteen months at sea (Leitwein et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A single generation of hatchery rearing is generally insufficient to cause genetic differentiation between captive and wild salmon (Gavery, Nichols, Goetz, Middleton, & Swanson, 2018; Le Luyer et al, 2017), though SNPs associated with domestication have been detected after several generations of hatchery rearing in Atlantic salmon (Harder & Christie, 2022). However, the hatchery environment has been shown to induce transcriptional changes in steelhead ( Oncorhynchus mykiss ; Christie, Marine, Fox, French, & Blouin, 2016), Atlantic salmon (Frisk et al, 2020), and Coho salmon ( O. kisutch ; Leitwein et al, 2022). This led to the idea that epigenetic mechanisms controlling gene expression, such as DNA methylation, may serve as the molecular mechanisms underlying rapid phenotypic shifts and fitness declines in hatchery environments.…”
Section: Introductionmentioning
confidence: 99%
“…It is difficult to note the extent to which strains within species differ; however, we note no large differences among the five strains of Atlantic salmon for which percentage of genes as DEGs could be calculated, and extensive overlaps between DEGs under domestication is observed where multiple strains are included in a single study [27]. The large estimate of DEGs under domestication in hatchery Coho salmon [47] deserves comment. This was the only study to examine fully sexually mature individuals, and individuals that had completed the at-sea proportion of the anadromous life cycle.…”
Section: Differences Between Studies Are Partially Explained By Tissu...mentioning
confidence: 99%